New Insights into the Role of Inflammatory Pathways and Immune Cell Infiltration in Sleep Deprivation-Induced Atrial Fibrillation: An Integrated Bioinformatics and Experimental Study - Liang J; Tang B; Shen J; Rejiepu M; Guo Y; Wang X; Shao S; Guo F; Wang Q; Zhang L (Journal of Inflammation Research)
Junqing Liang,1,2 Baopeng Tang,1,2 Jun Shen,1,2 Manzeremu Rejiepu,1,2 Yankai Guo,1,2 Xiaoyan Wang,1,2 Shijie Shao,1,2 Fei Guo,3 Qin Wang,4 Ling Zhang1 1Xinjiang Key Laboratory of Cardiac Electrophysiology and Cardiac Remodeling, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 2Cardiac Pacing and Electrophysiology Department, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 3Department of Cardiology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People’s Republic of China; 4Department of Geriatrics and Cadre Ward, Second Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of ChinaCorrespondence: Qin Wang; Ling Zhang, Email w2036661q@126.com; ydzhangling@126.comBackground: The common occurrence of atrial fibrillation (AF) as a cardiac arrhythmia, along with its link to sleep deprivation (SD), is gaining more acknowledgment. Even with progress in comprehending the development of AF, the molecular connections between SD and AF are still not well-defined. The objective of this research was to pinpoint the shared molecular routes responsible for SD-induced AF and investigate possible treatment targets.Methods: Utilizing bioinformatics, we examined two transcriptome datasets from the Gene Expression Omnibus (GEO) database to pinpoint genes with differential expression (DEGs) common to SD and AF. Analyses focusing on functional enrichment, such as Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), were conducted to pinpoint crucial biological mechanisms and pathways. Furthermore, we utilized immunofluorescence and Western blot techniques to evaluate YBX1 expression and its role in activating NLRP3 inflammasomes in a rat model induced by SD.Results: A total of 540 common DEGs were precisely identified between the AF and SD data collections. Studies emphasizing functional enrichment have highlighted the significance of inflammation pathways, particularly the NOD-like receptor signaling route. The application of machine learning uncovered four crucial genes—CDC5L, MAPK14, RAB5A, and YBX1—with YBX1 becoming the predominant gene in diagnostic processes. Investigating immune penetration revealed significant connections between YBX1 expression and specific immune cell types, notably CD8+ T cells and M1 macrophages. Live studies have demonstrated that SD amplifies the atrial electrical rearrangement, structural changes, the infiltration of inflammatory cells, and the heightened presence of YBX1 along with inflammasome elements.Conclusion: The research pinpoints YBX1 as a crucial gene in SD-related AF, possibly influencing its impact via the NOD-like receptor signaling route and the invasion of immune cells. The results offer crucial understanding of the molecular processes behind AF and propose YBX1 as a possible treatment focus to reduce the risk of AF caused by SD.Keywords: atrial fibrillation, sleep deprivation, bioinformatic analysis, inflammation, YBX1